2014
DOI: 10.1080/02188791.2014.961899
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service education for primary school English teachers in Indonesia: policy implications

Abstract: Although English is only an extra-curricular subject at primary level in Indonesia, expectations over the improved quality of the teachers are exceptionally high . This is the case in the past few years in which the low proficiency of primary English teachers and their lack of teaching competencies have repeatedly been pointed out as major constraints. Unfortunately, it remains unclear whether this problem is attributed to the delivery of pre-service education in preparing primary school English teachers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 14 publications
4
32
0
Order By: Relevance
“…While suggestions have been made to overhaul pre-service education in order to better prepare student teachers to teach English at elementary level (Zein, 2014), specific measures that indicate how this can be undertaken at pre-service level are yet to be seen. Directions for better preparation of graduates of teacher training colleges and English departments to teach English at elementary level remain obscure.…”
Section: Has the Pre-service Education Been Effective?mentioning
confidence: 99%
See 1 more Smart Citation
“…While suggestions have been made to overhaul pre-service education in order to better prepare student teachers to teach English at elementary level (Zein, 2014), specific measures that indicate how this can be undertaken at pre-service level are yet to be seen. Directions for better preparation of graduates of teacher training colleges and English departments to teach English at elementary level remain obscure.…”
Section: Has the Pre-service Education Been Effective?mentioning
confidence: 99%
“…Zein (2014) argued that the pre-service streams overall fail to provide maximum support to prepare elementary teachers to deliver successful English instruction. The inadequacy of pre-service level education in preparing professional English teachers with good skills and knowledge to teach at elementary level largely contributes to this situation.…”
Section: Has the Pre-service Education Been Effective?mentioning
confidence: 99%
“…Those teachers are trained to teach in secondary level. Their ability in teaching pre-primary and primary level is largely unknown [6]. For the purpose of this study, pre-primary and primary level roughly from the age of 4 up to 12 years old, for kindergarten and elementary students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…English language proficiency knowledge, and knowledge and skills related to curriculum, syllabus, language testing and assessment, teaching methodology, teaching skills, and material development are acquired by teachers graduated from English Education Department [6]. Some colleges for teacher's training and education offer English for young learners in their curriculum, while some do not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to previous studies conducted in Indonesia, many English teachers in Indonesian elementary schools employed a rather monotonous lecture method and seldom varied their teaching methods (Dardiri, 1994;Hawanti, 2011;Mardika, 2008;Rachmajanti, 2008;Sugeng, 2000;Zein, 2012). Rachmajanti (2008) revealed that most students in the Indonesian elementary schools were unsatisfied with the teacher-centered instructional method adopted by many Indonesian English teachers and preferred to work in small groups with interactive learning activities.…”
Section: Introductionmentioning
confidence: 99%